2013
DOI: 10.1111/ppl.12013
|View full text |Cite
|
Sign up to set email alerts
|

Linking genes of unknown function with abiotic stress responses by high‐throughput phenotype screening

Abstract: Over 13% of all genes in the Arabidopsis thaliana genome encode for proteins classified as having a completely unknown function, with the function of >30% of the Arabidopsis proteome poorly characterized. Although empirical data in the form of mRNA and proteome profiling experiments suggest that many of these proteins play an important role in different biological processes, their functional characterization remains one of the major challenges in modern biology. To expand the annotation of genes with unknown f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(94 citation statements)
references
References 41 publications
2
83
0
3
Order By: Relevance
“…7B). OsAP37-activated genes such as ICL, RLD, E3UL, RcbX, and Dfu584 are known to play a crucial role in carbon metabolism and photosynthesis under drought stress (Kwak et al, 2007;Lee et al, 2009;Kolesi nski et al, 2011;Luhua et al, 2013;Wang et al, 2014). The high induction under drought of GUDK in the flag leaf and reduced photosynthesis in the mutant lines suggest that GUDK regulates photosynthesis and carbon metabolism genes by phosphorylating OsAP37, Table I.…”
Section: Gudk Regulates Rice Yield By Potentially Transphosphorylatinmentioning
confidence: 99%
“…7B). OsAP37-activated genes such as ICL, RLD, E3UL, RcbX, and Dfu584 are known to play a crucial role in carbon metabolism and photosynthesis under drought stress (Kwak et al, 2007;Lee et al, 2009;Kolesi nski et al, 2011;Luhua et al, 2013;Wang et al, 2014). The high induction under drought of GUDK in the flag leaf and reduced photosynthesis in the mutant lines suggest that GUDK regulates photosynthesis and carbon metabolism genes by phosphorylating OsAP37, Table I.…”
Section: Gudk Regulates Rice Yield By Potentially Transphosphorylatinmentioning
confidence: 99%
“…For example, we compared the mlDNApredicted salt-related and cold-related genes with the genes associated with a strong phenotypic response in their T-DNA mutation lines documented in a recent large-scale phenotype screening work (Luhua et al, 2013) and found 16 salt-related genes (AT5G41080, AT2G32210, AT1G02660, AT1G76600, AT1G55040, AT2G47710, AT3G14060, AT3G26470,AT3G60520, AT2G15560, AT3G29370, AT5G06130, AT2G34600, AT5G57340, AT3G46960, and AT1G18900) and 13 cold-related genes (AT2G32210, AT5G51570, AT2G40000, AT1G79660, AT5G62920, AT4G31730, AT1G78070, AT2G25250, AT1G16730, AT1G18850, AT4G34630, AT1G30200, and AT1G56230) that did not pass the statistical cutoff by either the t test, Limma, or SAM. In addition, there were 83 stress-related genes experimentally supported by the large-scale phenotypic screening work (Luhua et al, 2013), of which 19 were known stress-related genes in the positive sample set, and 64 were newly predicted by mlDNA (Supplemental Data Set 4). For all six types of stress, we found that the majority of stress-related genes were tissue specific, with 75 to 85% of the genes usually specific to either roots or shoots ( Figure 5C).…”
Section: The Candidate Stress-related Genes Predicted By Mldnamentioning
confidence: 99%
“…Orphans were enriched in differentially expressed gene sets from Arabidopsis (Arabidopsis thaliana) and rice (Oryza sativa) following treatments with hormones, abiotic, or biotic stressors (Guo et al, 2007;Donoghue et al, 2011). Arabidopsis mutant screens identified several plant orphan genes that alter abiotic stress resistance (Luhua et al, 2013). Examples detailing the functional role of orphan genes in plant disease responses are rare.…”
mentioning
confidence: 99%